Volume 3: Heat Transfer, Parts a and B 2009
DOI: 10.1115/gt2009-59380
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Annulus Performance Parameters on Rotor-Stator Cavity Sealing Flow

Abstract: The amount of cooling air assigned to seal high pressure turbine rim cavities is critical for performance as well as component life. Insufficient air leads to excessive hot annulus gas ingestion and its penetration deep into the cavity compromising disk or cover plate life. Excessive purge air, on the other hand, adversely affects performance. This paper is Part-2 of the authors’ work on ingestion reported last year [1]. Whereas, the main focus of that investigation was to qualitatively describe ingestion driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Previous studies (e.g. [3][4][5], [13][14] and others) have attributed the circumferential pressure asymmetries in the annulus as the driving mechanism for ingress. It was shown that as the annulus flow coefficient CF increased, the annulus pressure asymmetries (quantified by the peak-to-trough non-dimensional pressure variation, ΔCp,a) increased, and the ingress was generally enhanced.…”
Section: Gtp-22-1355mentioning
confidence: 96%
“…Previous studies (e.g. [3][4][5], [13][14] and others) have attributed the circumferential pressure asymmetries in the annulus as the driving mechanism for ingress. It was shown that as the annulus flow coefficient CF increased, the annulus pressure asymmetries (quantified by the peak-to-trough non-dimensional pressure variation, ΔCp,a) increased, and the ingress was generally enhanced.…”
Section: Gtp-22-1355mentioning
confidence: 96%
“…Zhou et al 3 reviewed previous computational studies related to ingress, including those by Hills et al, 4 Laskowski et al, 5 Rabs et al, 6 Johnson et al, 7 Wang et al, 8 Zhou et al 9 and Mirzamoghadam et al 10,11 A number of authors have noted that the statistical convergence for pressure variations in the annulus is more quickly and more easily obtained than the cooling effectiveness field in the wheel-space.…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%
“…In addressing both (a) and partly (b) objectives, the survey by Mirzamoghadam et al [8] in 2009 looked at the influence of turbine mainstream boundary conditions on the HP turbine disk cavity minimum sealing flow using 3D CFD. The periodic sector model runs were made using the steady state model with the mixing plane located aft of the cavity.…”
Section: Introductionmentioning
confidence: 99%